Involvement of Chloride Channels in IGF-I -induced Proliferation of Porcine Arterial Smooth Muscle Cells - Cheng, Gang (2006)
OBJECTIVE: The existence of Cl(-) channels in vascular smooth muscle cells (VSMCs) has been increasingly investigated, but the biological functions are not yet clear. Insulin-like growth factor (IGF)-I affects proliferation and migration of VSMCs, and dysregulation of this axis may be involved in atherogenesis and intimal hyperplasia. We examined the effects of Cl(-) channel blockers on IGF-I-induced proliferation in porcine VSMCs. The siRNA approach was used to support the role of ClC-2, a member of the volume-regulated Cl(-) channel family, in cell proliferation of VSMCs. METHOD AND RESULTS: The IGF-I-induced VSMC proliferation was significantly suppressed by the Cl(-) channel blockers NPPB and IAA94 but not by DIDS. IGF-I-induced cell proliferation parallel a significant increase in the endogenous expression of ClC-2 mRNA and protein. Inhibitors of PI 3-kinase, LY294002 and wortmannin, significantly attenuated the IGF-I-upregulated ClC-2 expression and cell proliferation. We observed ClC-2-like Cl(-) current, and this current was augmented by IGF-I. SiRNA specifically targeted to ClC-2 abolished IGF-I-induced cell proliferation. CONCLUSION: Our data demonstrate that ClC-2 plays a role in IGF-1-induced regulation of VSMC proliferation in cardiovascular diseases.